When ?conservation? leads to land degradation: lessons from Ban Lak Sip, Laos - Lesterlin, G.; Giordano, Mark; Keohavong, G. (International Water Management Institute, 2005)
In this report, we test the hypothesis that the primary factors behind the farming system changes in Ban Lak Sip lay not in the village itself but rather in the broader Laotian social, economic and political setting. The study uses an integrated approach that examines both the physical and social dimensions of land use and soil erosion in Ban Lak Sip within this broader system environment.